Hybridization potential among tomato accessions for pre‑breeding for resistance to late blight - Laurindo, Bruno Soares; Laurindo, Renata Dias Freitas; Nick, Carlos; Carneiro, Pedro Crescêncio Souza; Mizubuti, Eduardo Seiti Gomide; Silva, Derly José Henriques da (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate parents with hybridization potential for pre‑breeding of tomato (Solanum lycopersicum) for resistance to late blight. Six tomato accessions (BGH‑2102, BGH‑2117, BGH‑2127, BGH‑2130, BGH‑2332, and BGH‑2343) were used as resistant parents and 15 F1 hybrids originated from these parents. The design was a randomized complete block with three replicates. The plants were inoculated with a mixture of Phytophthora infestans sporangia, the etiological agent oflate blight, at a concentration of 5x103 sporangia mL‑1. The area under the disease progress curve was used to evaluate resistance. Diallelic analysis was performed, considering the effect of genotypes as fixed. The general and specific combining ability of the accessions was estimated. The resistance pattern of the parents and of most of the F1 was the same as that of the resistant controls. The following were observed: additive genetic variability among the parents, predominance of nonadditive gene effects, and bidirectional dominance deviations in the control of the trait. The frequency of favorable and divergent alleles for late blight resistance is higher in the BGH‑2117, BGH‑2127, and BGH‑2343 accessions.